Online Marketing Using Social Media Performed by Star-Up Entrepreneurs in Kediri Regency - Fika Dwi Rahmania; Budi Eko Soetjipto; Wening Patmi Rahayu (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims at finding out the reasons for start-up entrepreneur to do online marketing using social media, the entrepreneurial strategy used by start-up entrepreneur in doing online marketing using social media and the benefits that the start up entrepreneur get in doing online marketing using social media. This study uses in-depth interviews and documentation. The research type is qualitative with phenomenology approach. The subject of research is 5 start-up entrepreneurs of food and beverage business in Kediri regency. The reasons for using social media are various. First it is because competitors also use social media for marketing. Another reason is using social media will ease the marketers in getting direct feedback from consumers. Then, social media can reach wider scope of consumers, easy to use, and affordable. Strategies used include information strategy, sales promotion and advertising, and join the community. The benefits of using social media are the opportunity of having an instant and fast communication with consumers, businesses and products can be recognized by the public, there is an increase on the revenue received annually.Abstrak: Studi ini bertujuan untuk mengetahui alasan wirausaha pemula melakukan pemasaran online dengan media sosial, strategi wirausaha pemula melakukan pemasaran onilne dengan media sosial dan manfaat yang dirasakan wirausaha pemula melakukan pemasaran online dengan media sosial. Studi ini menggunakan metode wawancara mendalam dan dokumentasi. Jenis Penelitian adalah kualitatif dengan pendekatan fenomenologi. Subjek penelitian adalah lima wirausaha pemula makanan dan minuman di kabupaten Kediri. Alasan menggunakan media sosial antara lain karena kompetitor menggunakan media sosial untuk pemasaran, karena secara langsung mendapatkan feedback dari konsumen, jangkauan luas, mudah digunakan, dan biaya terjangkau. Strategi yang digunakan antara lain strategi informasi, promosi penjualan dan periklanan, serta bergabung dengan komunitas. Manfaat yang dirasakan antara lain komunikasi langsung dan cepat dengan konsumen, usaha dan produk dapat dikenal oleh masyarakat, meningkatnya pendapatan.